Facts about Fats and Oils - Tiffany N. Stodtko; Wendy J. Dahl (EDIS)
Fats and oils are important for good health. Fats provide your body with energy while oils are needed in the diet in small amounts because they are a major source of Vitamin E, which has antioxidant properties. This 4-page fact sheet describes the different types of fats and oils and tips for choosing the healthiest types. Written by Tiffany N. Stodtko and Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, June 2016.